PENGARUH PENANAMAN MODAL ASING (PMA), PENANAMAN MODAL DALAM NEGERI (PMDN), DAN ANGKATAN KERJA TERHADAP PERTUMBUHAN EKONOMI DI JAWA TENGAH - Yoga Krissawindaru Arta yoga krissawindaru (Economics Development Analysis Journal, 2013)
Foreign investment can be carried out this research with quantitative research, which in this study using quantitative methods with a scientific approach to managerial and economic decisions. This approach departs from the data which is then processed and manipulated this data into valuable information for decision-making (Kuncoro, 2007: 1). GDP is defined as the total value added generated by all business units within a particular area, or a total value of final goods and services produced by all economic units in an area. The level of investment has a positive relationship with economic growth. Foreign Direct Investment (FDI) and no significant negative effect on economic growth in the province of Central Java with a coefficient of -5.680308. Domestic Investment (DCI) and a significant positive effect on economic growth in the province of Central Java with a coefficient value of 3.388511. Labor Force (AK) positive and significant impact on economic growth in the province of Central Java with coefficient value of 27.44731. Research variables Foreign Investment (FDI), Domestic Investment (DCI), and the Labor Force (AK) is the same with or near-significant effect on economic growth in the province of Central Java.